Florentino Ameghino entre Luján et Moscou (1911-1954) - Irina Podgorny (Revue d’Histoire des Sciences Humaines)
Despite his reputation as the most famous scientist in twentieth-century Argentina, Florentino Ameghino (1853-1911) has remained paradoxically on the margins of international historiography. This article analyses the transformation of this major figure of late nineteenth-century science into an Argentinian national scholar. In the second part, we shall examine how the figure of the scholar was constructed during Cold War, specifically in light of the cultural politics of the Argentinian and Soviet Communist Parties, in which Ameghino was associated with Lyssenko and Michurin, and marshalled to counter dominant capitalist scientific theories. Setting the political instrumentalisation of the scholar in a transnational dimension, this article also discusses the major impact of the cult of Ameghino on the historiography of the sciences in Argentina.